Study on the Function of the Inositol Polyphosphate Kinases Kcs1 and Vip1 of Candida albicans in Energy Metabolism - Peng, Xueling; Yu, Qilin; Liu, Yingzheng; Ma, Tianyu; Li, Mingchun (Frontiers in Microbiology, 2020)
In Saccharomyces cerevisiae, the inositol polyphosphate kinase KCS1 but not VIP1 knockout is of great significance for maintaining cell viability, promoting glycolysis metabolism, and inducing mitochondrial damage. The functions of Candida albicans inositol polyphosphate kinases Kcs1 and Vip1 have not yet studied. In this study, we found that the growth rate of C. albicans vip1Δ/Δ strain in glucose medium was reduced, and the upregulation of glycolysis was accompanied by a decrease in mitochondrial activity, resulting in a large accumulation of lipid droplets, along with an increase in cell wall chitin and cell membrane permeability, eventually leading to cell death. Relieving intracellular glycolysis rate or increasing mitochondrial metabolism can reduce lipid droplet accumulation, causing a reduction in chitin content and cell membrane permeability. The growth activity and energy metabolism of the vip1Δ/Δ strains in a non-fermentable carbon source glycerol medium were not different from those of the wild-type strains, indicating that knocking out VIP1 did not cause mitochondria damage. Moreover, C. albicans KCS1 knockout did not affect cell activity and energy metabolism. Thus, in C. albicans, Vip1 is more important than Kcs1 in regulating cell viability, and energy metabolism.